Development of methods of cryopreservation of Verbascum officinalis’seeds - Tleukenova, S.U.; Baigarayev, D.Sh.; Atikeyeva, S.N.; Ramazanov А.K.; Gavrilkova H.А.; Musina, R.T. (Fundamental and Experimental Biology, 2020)
Introduction into the cryogenic collection of medicinal plant seeds allows maintaining their viability for a long time. However, there are no universal protocols for freezing seeds of plants; so for each species, the freezing and defrosting conditions need to be selected individually. The purpose of the present studies is to determine the main conditions for cryopreservation of the seeds of the medicinal plant Verbascum officinalis. During the development of the cryopreservation condition, optimal freezing containers, defrosting temperature, prefreezing humidity of seeds and optimal cryoprotectors were selected. The results of the studies showed that the maximum germination rates of seeds and germination energy were obtained using plastic containers, seeds humidity of 3 %, defrosting in a water bath. The optimal cryoprotector is DMSO in concen-tration 5 %. The results made it possible to introduce Verbascum officinalis into the cryogenic collection of seeds of medicinal plants.